Getting to Sweden, Part II: Breaking with Corruption in the Nineteenth Century. (15th March 2015) - Rothstein, Bo; Teorell, Jan
<x xml:space="preserve">Abstract</x> Issues about corruption and other forms of 'bad government' have become central in large parts of the social sciences. An unresolved question, however, is how countries can solve the issue of systemic corruption. In this article, based on Elinor Ostrom's theory of common pool resource appropriation, a new theoretical model for explaining this type of institutional change is developed. Sweden during the nineteenth century is used as an illustration of the model by showing how the country made a transition from being largely patrimonial, nepotistic and corrupt to a modern, Weberian, efficient and impartial state structure. Building upon a companion article about the importance of losing a war as a precondition for breaking systematic corruption, this article stresses the importance of three additional factors in Sweden: previous changes in courts and the legal system; recognition of the problem by the main contemporary political actors as shown in debates in the Diet; and the new liberal ideology that made an important impact on the Swedish political scene during this period.